Pengaruh Kepemilikan Manajerial, Investment Opportunity Set (IOS), Leverage Dan Ukuran Perusahaan Terhadap Kualitas Laba - Winda Mulyani; Dirvi Surya Abbas; Hamdani, Hamdani; Triana Zuhrotun Aulia (Pusat Riset dan Inovasi Nasional, 2022)
The study aims to test empirically the effect of managerial ownership, ios, leverage and firm size on earnings quality in consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period. sampling technique using purposive sampling technique. based on predetermined criteria obtained 12 manufacturing companies. the type of data used is panel data regression analysis using the eviews 12,0 data processing program. The results show that managerial ownership, ios and leverage have no effect on earnings quality. While firm size has a positive effect on earnings quality.